Upaya Menerapkan Standar Pelayanan Minimal di Bidang Kesehatan Berdasarkan Indikator Pelayanan Kesehatan Hipertensi di Puskesmas Kota Semarang - Anindya, Prakasita Artha; Jati, Sutopo Patria; Nandini, Nurhasmadiar (Jurnal Ilmiah Mahasiswa, 2020)
Title : Efforts to Apply Minimum Health Service Standards in Hypertension Health Services Indicators in Public Health Services of Semarang CityBackground: Minimum services standards have to be provided by each region to their citizen regarding the minimum type and quality of basic services. Minimum health service standard have 12 type of basic services. One of them are the health service of hypertension patient which was only 24,75% in 2017 from target 100% in Semarang District. Methods: The research objective was to analyse the implementation of minimum service standards. A qualitativemethod and a descriptive analytic approach was used in this research.Primary data from in-depth interviews and secondary data that were relevant to the research   were collected. The study was conducted at Public Health Services of Gunungpati, Ngesrep, Pudak Payung, Sekaran and Health Office ofSemarang City.  The respondents wereprovider staff at Public Health Services and Health Office holding the non-infection disease program. To get properly information this study also interviewing the patients. Result: The results showed the Minister of Health’s Regulation Number 4/ 2019 concerning minimum service standards in the health sector was too ideal and was it difficult to reach. Conclusions: Public Health servicesas the executor of the Minister of Health Regulation Number 4/2019 must have innovations in order to achieve the 100% target.